A Comparative Analysis of English Language Education in Nepalese and Finnish Basic Education Curricula - Adhikari, Bala Ram (The EFFORTS, Journal of Education and Research, 2024)
This article explored the objectives, contents, and pedagogical approaches in English language education examining the Finnish and Nepalese basic education curricula. The study aimed to reveal the similarities and differences between two countries’ English language curricula and to find out why a big difference occurs between Finland’s and Nepal’s English proficiency levels. Data were collected from Finland’s and Nepal’s English language curricula for basic education and the official documents such as acts, decrees, and laws on basic education were also examined to support the data from the curricula. Data were analyzed with the method of thematic document analysis. Overall, the results of the comparative study indicate that both Finland and Nepal aim to increase linguistic and cultural awareness and teach English language for communicative competence. Both countries also would like to encourage pupils to track their English language learning. On the other hand, while the Finnish curriculum offers general guidelines for the instruction of the English language giving flexibility and autonomy to schools, the Nepalese curriculum prevents schools from preparing a flexible plan for English language teaching according to the needs of pupils by offering specific content and testing techniques. The findings reveal that the Finnish curriculum presents guidelines for teachers, students, and local education providers on how to reach educational goals rather than giving specific content for the subjects giving flexibility and autonomy to schools. On the other hand, the Nepalese curriculum provides specific instructions and suggestions for the application of English language teaching with detailed content containing units for each grade and even suggested testing techniques for teachers.